Catching the imposter in the brain: The case of Capgras delusion. (October 2020) - Nuara, Arturo; Nicolini, Ylenia; D'Orio, Piergiorgio; Cardinale, Francesco; Rizzolatti, Giacomo; Avanzini, Pietro; Fabbri-Destro, Maddalena; De Marco, Doriana
Abstract: Here we describe a rare case of Capgras delusion – a misidentification syndrome characterized by the belief that a person has been replaced by an imposter – in a patient without evident neurological or psychiatric symptoms. Intriguingly, delusional belief was selective for both person and modality, as the patient believed that his son – not his daughter or other relatives – was substituted with an imposter only while being in presence of him and looking at his face, but not when merely listening to his voice. A neuroanatomical reconstruction obtained integrating morphological and functional patient's neuroimaging data highlighted two main peculiarities: a compression of the rostral portion of right temporal lobe due to a large arachnoid cyst, and a bilaterally reduced metabolism of frontal areas. Autonomic data obtained from thermal infra-red camera and skin conductance recordings showed that a higher sympathetic activation was evoked by the observation of daughter's face, relative to the observation of the son's face as well as of not-familiar faces; conversely, daughter and son voices elicited a similar sympathetic activation, higher relative to not-familiar voices, indicating a modality-dependent dissociation consistent with the delusional behavior. Our case supports the "two-hit hypothesis" about Capgras delusion etiopathogenesis: here, the first hit is represented by the right-temporal lesion impairing the association between familiar faces and emotional values, the second one is the frontal bilateral hypometabolism favoring delusional behavior. The selective occurrence of "imposter" delusion for a particular subject and for a specific perceptual modality suggests the involvement of modality-specific interactions in the retrieval of affective properties during familiar people recognition.